High-field/high-frequency EPR spectroscopy on synthetic melanin: on the origin of carbon-centered radicals. Issue 19 (10th August 2021) - Paulin, J. V.; Batagin-Neto, A.; Naydenov, B.; Lips, K.; Graeff, C. F. O.
Abstract : High-field/high-frequency electron paramagnetic resonance spectroscopy was employed to synthesize melanin to provide relevant information on the carbon-centered free-radical nature of this biomaterial. Abstract : Among all the pigments found in nature, melanin has drawn considerable attention for bioelectronics applications as it contains a set of physicochemical properties such as antioxidant activity, metal chelation, biocompatibility, broad-band absorbance throughout the UV-visible region, hydration-dependent conductivity and intrinsic and extrinsic free radical character. A better understanding of these properties is a matter of significant importance to improve melanin-based organic devices efficiently. Therefore, the origin of melanin free-radicals was studied using continuous-wave electron paramagnetic resonance (EPR) spectroscopy at 263 GHz for standard non-functionalized and sulfonated derivatives. Our results indicated that more than one radical species should be evoked to study the free-radical nature of standard and sulfonated melanin. Additionally, we also confirm that the free-radical system of sulfonated melanin is similar to non-functionalized melanin. Based on the g -anisotropy analysis, we propose which potential units could be responsible for carbon-centered radicals.